Umiejętności w zakresie kształtowania strategii personalnej oraz realizowania polityki kadrowej jako kluczowe wyznaczniki identyfikujące kandydata na stanowisko dyrektora biblioteki = Skills in developing personnel strategy and implementing personnel policy as key determinants identifying a candidate for the position of the library director - Wojciechowska, Maja (Zielona Góra: "Pro Libris" Wydawnictwo Wojewódzkiej i Miejskiej Biblioteki Publicznej w Zielonej Górze)
This article presents the issue of shaping personnel strategy and implementing personnel policy as a competency important for those aspiring for the position of a library director. The library director's activities are discussed, including the range of tangible and intangible resources under his or her control, the assumptionsof personnel strategy as a tool for shaping the library by the director and managers, organizational values in the library, the issue of interpersonal communication and communication behaviour of managers, and the problem of motivational skills as a managerial competence.
Keywords: dyrektor biblioteki; strategia personalna; polityka personalna; zarządzanie biblioteką; library director; personnel strategy; personnel policy; library management